2018
DOI: 10.1051/0004-6361/201834417
|View full text |Cite
|
Sign up to set email alerts
|

Chemical segregation of complex organic O-bearing species in Orion KL

Abstract: We investigate the chemical segregation of complex O-bearing species (including the largest and most complex ones detected to date in space) towards Orion KL, the closest high-mass star-forming region. The molecular line images obtained using the ALMA science verification data reveal a clear segregation of chemically related species depending on their different functional groups. We map the emission of 13CH3OH, HCOOCH3, CH3OCH3, CH2OCH2, CH3COOCH3, HCOOCH2CH3, CH3CH2OCH3, HCOOH, OHCH2CH2OH, CH3COOH, CH3CH2OH, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 52 publications
(90 reference statements)
6
61
0
Order By: Relevance
“…We note that t-C 2 H 5 OCH 3 was tentatively detected in several high-mass sources, such as W51 e1/e2 (Fuchs et al 2005), which was refuted by Carroll et al (2015) and Orion KL (Tercero et al 2015). Later, Tercero, B. et al (2018) confirmed the detection towards the Orion KL compact bridge region. The last study reported a rotational temperature of 150±20 K and a column density of 3.0 ± 0.9 × 10 15 cm −2 , leading to an abundance of 3.7 × 10 −9 with respect to H 2 .…”
Section: New Detectionssupporting
confidence: 78%
“…We note that t-C 2 H 5 OCH 3 was tentatively detected in several high-mass sources, such as W51 e1/e2 (Fuchs et al 2005), which was refuted by Carroll et al (2015) and Orion KL (Tercero et al 2015). Later, Tercero, B. et al (2018) confirmed the detection towards the Orion KL compact bridge region. The last study reported a rotational temperature of 150±20 K and a column density of 3.0 ± 0.9 × 10 15 cm −2 , leading to an abundance of 3.7 × 10 −9 with respect to H 2 .…”
Section: New Detectionssupporting
confidence: 78%
“…This will allow us to select the important chemical paths between species and possibly constrain the chemistry of COMs. Recently, Tercero et al (2018) have suggested segregation of various O-bearing COMs based on spatial variation inside BN-KL. Including the channel information presented in this work, combined with quantitative estimates, which require the inclusion of zero-spacing data that is not yet available, will allow us to follow the abundance variations of each species along the expanding paths and better understand the chemistry in hot cores, both in the gas phase and on grain surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only the first two vibration states (HC 3 N, v 7 = 2 and H 13 CCCN, v 7 = 1, HC 13 CCN, v 7 = 1 and HCC 13 CN, v 7 = 1 ) were tentatively detected towards AFGL 4176. Tercero et al (2018) also investigate the inventory of complex molecules towards Orion KL, this timed focussing on O-bearing species. With a resolution of ∼1.5 , they probe spatial scales of ∼620 au.…”
Section: Comparison With the High-mass Star-forming Regions Inmentioning
confidence: 99%
“…With a resolution of ∼1.5 , they probe spatial scales of ∼620 au. Tercero et al (2018) derive molecular abundances at three locations. These are selected based on where each of the species methylformate, ethylene glycol, and ethanol peak.…”
Section: Comparison With the High-mass Star-forming Regions Inmentioning
confidence: 99%
See 1 more Smart Citation